Effect of the grapevine leafroll virus on the mineral composition of leaf petiole and blade of Cabernet Franc variety - Miele, Alberto; Kuhn, Gilmar B.; Tonietto, Jorge; Volkweiss, Sérgio J. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determine the effect of the grapevine leafroll on the mineral composition of leaf petiole and blade of Vitis vinifera L. cv. Cabernet Franc. This experiment was conducted in Bento Gonçalves, RS, Brazil, during the 1979/80 vegetative cycle. The grapevines, eight years old, were conducted in the pergola system and were grafted on V. riparia x V. rupestris 101-14 Mgt. The experimental design was completely randomized, with three treatments and five replicates. The treatments tested were: a. healthy grapevines; b. mildly infected grapevines; and c. severely infected grapevines. The leaves were collected during the flowering period. The results show that the grapevines severely infected with this virus disease presented petioles with lower values of total N, P, Ca, Mg, Mn, Cu, Fe, and Zn, when compared with the healthy ones, whereas the NO3 -N had a tendency to decrease. However, the K contents increased. The results related to leaf blades are generally similar to the values obtained in the petioles.